Analyzing conformational changes in single FRET-labeled A1 parts of archaeal A1AO-ATP synthase - Sielaff, Hendrik (2018)
ATP synthases utilize a proton motive force to synthesize ATP. In reverse, these membrane-embedded enzymes can also hydrolyze ATP to pump protons over the membrane. To prevent wasteful ATP hydrolysis, distinct control mechanisms exist for ATP synthases in bacteria, archaea, chloroplasts and mitochondria. Single-molecule Förster resonance energy transfer (smFRET) demonstrated that the C-terminus of the rotary subunit ε in the Escherichia coli enzyme changes its conformation to block ATP hydrolysis. Previously, we investigate the related conformational changes of subunit F of the A1AO-ATP synthase from the archaeon Methanosarcina mazei Gö1. Here, we analyzed the lifetimes of fluorescence donor and acceptor dyes to distinguish between smFRET signals of conformational changes and potential artefacts.